2022
DOI: 10.2340/jrm.v54.1379
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Clinically Important Functional Impairments and Rehabilitation Needs in Cancer Survivors and a Pilot Validation of the Cancer Rehabilitation Questionnaire

Abstract: Objectives: Despite the availability of cancer rehabilitation, utilization at our institution was low. We designed the Cancer Rehabilitation Questionnaire (CRQ) to investigate the prevalence of functional impairments amongst cancer survivors and attitudes towards rehabilitation participation. We evaluated the performance of CRQ as a screening tool for detecting clinically important physical dysfunction.Design: A cross-sectional study was performed, recruiting cancer survivors at a university outpatient oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies have been identified from across WHO regions, but were predominantly conducted in North America and Europe: African Region (Cameroon, The Gambia, Eritrea), the Eastern Mediterranean Region (Egypt), the South-East Asia Region (India, Thailand), the Region of the Americas (Canada, Chile, USA), the Western Pacific Region (Australia, Singapore) and the European Region (Denmark, Germany, UK, Sweden). In terms of study design, a variety of studies have been included, from observational cross-sectional studies [43][44][45][46][47][48][49][50][51] and cohort studies, [52][53][54][55][56][57][58] over secondary data analysis of population studies, 59 descriptions of tool development 60 61 and algorithm development from machine learning, 62 to prospective observational studies [63][64][65][66] and longitudinal studies. [67][68][69][70] Rehabilitation needs screening In total, 24 rehabilitation need screening tools or assessments have been identified from the 31 included papers.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Studies have been identified from across WHO regions, but were predominantly conducted in North America and Europe: African Region (Cameroon, The Gambia, Eritrea), the Eastern Mediterranean Region (Egypt), the South-East Asia Region (India, Thailand), the Region of the Americas (Canada, Chile, USA), the Western Pacific Region (Australia, Singapore) and the European Region (Denmark, Germany, UK, Sweden). In terms of study design, a variety of studies have been included, from observational cross-sectional studies [43][44][45][46][47][48][49][50][51] and cohort studies, [52][53][54][55][56][57][58] over secondary data analysis of population studies, 59 descriptions of tool development 60 61 and algorithm development from machine learning, 62 to prospective observational studies [63][64][65][66] and longitudinal studies. [67][68][69][70] Rehabilitation needs screening In total, 24 rehabilitation need screening tools or assessments have been identified from the 31 included papers.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Less than half of those surveyed reported reduction of adverse effects as an impetus to exercise [ 20 ]. Similarly, another survey reported 54% of those presenting with functional impairments were not willing to undergo rehabilitation [ 21 ], reflecting a need for better education. While supervised centre-based programmes have advantages in enhancing adherence to exercise, home-based exercise programmes are convenient and effective as well [ 22 ].…”
Section: Introductionmentioning
confidence: 99%